Important of Accounting of Human Assets and Its Challenges A Field Study on Misurata University: دراسة ميدانية على جامعة مصراتة (Journal of Academic Research, 2025)
The paper aimed to shed light on the extent to which Misurata University is aware of the importance of accounting for human assets and to identify the most important obstacles that may prevent its implementation. The study relied on the descriptive analytical approach by distributing an electronic questionnaire to the study community, which numbered 41 individuals, and the response rate was about 83%. After receiving the respondents' responses, the necessary statistical tests were conducted to verify the study sample and the stability and validity of the study tool using the SPSS program. The (t test) was relied upon to test the hypotheses. The study reached a set of results, the most important of which are: Misurata University's awareness of the importance of accounting for human assets. The study recommended the necessity of increasing awareness of the importance of adopting one of the models for measuring human assets and working to improve the accounting system to have the necessary components for its implementation.